2022
DOI: 10.1101/2022.11.09.515803
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microstimulation of sensory cortex engages natural sensory representations

Abstract: Cortical activity patterns occupy a small subset of possible network states. If this is due to intrinsic network properties, microstimulation of cortex should evoke activity patterns resembling those observed during natural sensory input. Here, we use optical microstimulation of virally transfected layer 2/3 pyramidal neurons in mouse primary vibrissal somatosensory cortex to compare artificially evoked activity with natural activity evoked by whisker touch and movement ('whisking'). We find that photostimulat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Touch-whisking interactions are likely more complex: whisking activity decorrelates vS1 activity 59 and likely increases sensitivity to external input. By directly activating touch-whisking neurons, whisking network activity may predispose the touch network towards stronger touch responses via pattern completion 34,35 (Figure 7H). The converse may also be true: touch activity could influence whisking networks via touch-whisking neurons, potentially driving movement adjustments as object contacts are made 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Touch-whisking interactions are likely more complex: whisking activity decorrelates vS1 activity 59 and likely increases sensitivity to external input. By directly activating touch-whisking neurons, whisking network activity may predispose the touch network towards stronger touch responses via pattern completion 34,35 (Figure 7H). The converse may also be true: touch activity could influence whisking networks via touch-whisking neurons, potentially driving movement adjustments as object contacts are made 49 .…”
Section: Discussionmentioning
confidence: 99%
“…What is the source of this increasing activity? Cortical excitatory circuitry is organized into assemblies 29 that exhibit high levels of recurrence 30 , with neurons that represent the same sensory input [31][32][33] exhibiting elevated connectivity, enabling pattern completion [34][35][36] and amplification 37 . Consequently, even small additions of spikes can bias ongoing activity 38 , movement 39 , and perception 40,41 .…”
Section: Introductionmentioning
confidence: 99%
“…Correlated spontaneous L2/3 calcium activity predicts connectivity 28,51,52 . In vS1, declines in touch responsiveness following touch neuron ablation 53 and channeling of activity towards natural touch responsive populations 54 point to elevated connectivity among touch neurons. Physically, then, a subset of neurons exhibiting elevated connectivity and greater long-term stability may act as a scaffold for less stable neural activity.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have used twophoton imaging to measure the activity of neurons in primary sensory areas during detection of a spot-like optogenetic photostimulation. One study showed that over the course of training sessions, an optogenetic spot stimulation in S1 increasingly engaged the touch-related neuronal assemblies in this area, disproportionally more than the whisking-related neurons (45). In another study focusing on the primary visual cortex (46), neurons recorded in the cortical area below the stimulation spot developed a specific tuning for the single spot compared to other stimulation patterns.…”
Section: Neuronal Substrate Of the Selectivity To Distributed Patternsmentioning
confidence: 99%